Comparison of vancomycin and linezolid in patients with peripheral vascular disease and/or diabetes in an observational European study of complicated skin and soft-tissue infections due to methicillin-resistant Staphylococcus aureus. (1st September 2015) - Eckmann, C.; Nathwani, D.; Lawson, W.; Corman, S.; Solem, C.; Stephens, J.; Macahilig, C.; Li, J.; Charbonneau, C.; Baillon-Plot, N.; Haider, S.
Abstract: Suboptimal antibiotic penetration into soft tissues can occur in patients with poor circulation due to peripheral vascular disease (PVD) or diabetes. We conducted a real-world analysis of antibiotic treatment, hospital resource use and clinical outcomes in patients with PVD and/or diabetes receiving linezolid or vancomycin for the treatment of methicillin-resistant Staphylococcus aureus complicated skin and soft-tissue infections (MRSA cSSTIs) across Europe. This subgroup analysis evaluated data obtained from a retrospective, observational medical chart review study that captured patient data from 12 European countries. Data were obtained from the medical records of patients ≥ 18 years of age, hospitalized with an MRSA cSSTI between 1 July 2010 and 30 June 2011 and discharged alive by 31 July 2011. Hospital length of stay and length of treatment were compared between the treatment groups using inverse probability of treatment weights to adjust for clinical and demographic differences. A total of 485 patients had PVD or diabetes and received treatment with either vancomycin ( n = 258) or linezolid ( n = 227). After adjustment, patients treated with linezolid compared with vancomycin respectively had significantly shorter hospital stays (17.9 ± 13.6 vs. 22.6 ± 13.6 days; p < 0.001) and treatment durations (12.9 ± 7.9 vs. 16.4 ± 8.3 days; p < 0.001). The proportions of patients prescribed oral, MRSA-active antibiotics at discharge were 43.2% and 12.4% of patients in the linezolid and vancomycin groups, respectively (p < 0.001). The reduction in resource use may result in lower hospital costs for patients with PVD and/or diabetes and MRSA cSSTIs if treated with linezolid compared with vancomycin.